Can mean platelet volume have predictive value in premature retinopathy? (Annals of Medical Research, 2021)
Aim: Retinopathy of prematurity, a proliferative vitreoretinopathy resulting from the vascular disorder of the retina, is the most frequent cause of blindness in childhood. In the pathogenesis of the disease, in particular, there are stages developing diametrically opposite to each other (the first phase vasoobliteration, the second phase neovascularization) helped our thoughts of the disease to form. Premature retinopathy is quite an important problem in newborn units not only as far as its consequences but also its follow-up and management. Our controlled clinical study aims to present a simple method that will facilitate the follow-up of the disease while guiding clinicians in predicting the prognosis of the disease.